"This show does not represent the views of the artists": Translation, non-translation, activism and access in the Homeland graffiti hack. Issue 1 (2nd January 2017) - Strowe, Anna
ABSTRACT: The October 2015 hack of the television show Homeland by three graffiti artists hired by the production company is a fascinating case of linguistic and translational activism. This article examines the event from several perspectives in translation studies, exploring how the brief creates space for the artists' action as well as how their work intersects with notions of narrative irony, linguistic and cultural hospitality and hijacking, media access, and authenticity. The case reveals how the work of the artists challenges the narrative spaces of the show while still fulfilling the given task. It shows the power of linguistic access, and illustrates how forms of access can be manipulated by activists in order to achieve wider dissemination. The analysis intersects with certain discourses on intersemiotic translations and multimodal texts, and considers the relationship between writing as verbal expression and writing as visual image.